Reproductive performance of three Iranian sheep breeds - Kiyanzad, M.R.; Panandam, J.M.; Emamjomeh Kashan, N.; Jelan, Z.A.; Dahlan, I. (Asian-Australasian Association of Animal Production Societies, 2003)
To evaluate the ewe reproductive performances of three Iranian local sheep breeds, namely Moghani, Chal and Zel, 27 rams and 473 ewes were used as the foundation flock in a crossbreeding program. The three breeds were crossed amongst themselves reciprocally. Ram breed and ewe breed showed a two-way interaction on apparent fertility. The Zel ewes showed higher fertility than the Chal and Moghani ewes (94.4 vs 77.3 and 84.6%). Prolificacy among main and individual mating groups were not significantly different (p>0.05). Zel ewes were 22.3 and 14.8% more reproductive (p<0.05) than Chal and Moghani ewes, respectively. Zel and Moghani ewes showed higher (p<0.05) ewe productivity than Chal ewes. Ram breed had a significant (p<0.05) effect on ewe efficiency. The Zel rams were not completely successful to mate with Chal ewes, this caused a to way-interaction between ram and ewe breeds. The Zel ewes mated with Chal and Moghani rams showed 26.1 and 28.5% more efficiency than those mated with Zel rams. This observation strongly supports the use of crossbreeding to improve the efficiency of the Zel ewes. With decreasing lamb mortality, through supplemented feeding of lambs in pre-weaning period, and increasing litter weight, through crossbreeding, it should be possible to improve the efficiency of Zel ewes even better than Chal and Moghani ewes. Small body size of Zel ewes that needs the lower maintenance requirements would be a well advantageous to using Zel ewes as the dam herd to produce commercial lambs in north area of Iran.